SFRP-4 abrogates Wnt-3a-induced ß-catenin and Akt/PKB signalling and reverses a Wnt-3a-imposed inhibition of in vitro mammary differentiation - Constantinou, T.; Baumann, F.; Lacher, M.; Saurer, S.; Friis, R.; Dharmarajan, Arunasalam (2008)
Background: Conserved Wnt ligands are critical for signalling during development; however, various factors modulate their activity. Among these factors are the Secreted Frizzled-Related Proteins (SFRP). We previously isolated the SFRP-4 gene from an involuting rat mammary gland and later showed that transgenic mice inappropriately expressing SFRP-4 during lactation exhibited a high level of apoptosis with reduced survival of progeny. Results: In order to address the questions related to the mechanism of Wnt signalling and its inhibition by SFRP-4 which we report here, we employed partially-purified Wnt-3a in a co-culture model system. Ectopic expression of SFRP-4 was accomplished by infection with a pBabepuro construct. The co-cultures comprised Line 31E mouse mammary secretory epithelial cells and Line 30F, undifferentiated, fibroblast-like mouse mammary cells. In vitro differentiation of such co-cultures can be demonstrated by induction of the ß-casein gene in response to lactogenic hormones. We show here that treatment of cells with partially-purified Wnt-3a initiates Dvl-3, Akt/PKB and GSK-3ß hyperphosphorylation and ß-catenin activation. Furthermore, while up-regulating the cyclin D1 and connexin-43 genes and elevating transepithelial resistance of Line 31E cell monolayers, Wnt-3a treatment abrogates differentiation of co-cultures in response to the lactogenic hormones prolactin, insulin and glucocorticoid. Cells which express SFRP-4, however, are largely unaffected by Wnt-3a stimulation. Since a physical association between Wnt-3a and SFRP-4 could be demonstrated with immunoprecipitation/Western blotting experiments, this interaction, presumably owing to the Frizzled homology region typical of all SFRPs, explains the refractory response to Wnt-3a which was observed. Conclusion: This study demonstrates that Wnt-3a treatment activates the Wnt signalling pathway and interferes with in vitro differentiation of mammary co-cultures to ß-casein production in response to lactogenic hormones. Similarly, in another measure of differentiation, following Wnt-3a treatment mammary epithelial cells could be shown to up-regulate the cyclin D1 and connexin-43 genes while phenotypically they show increased transepithelial resistance across the cell monolayer. All these behavioural changes can be blocked in mammary epithelial cells expressing SFRP-4. Thus, our data illustrate in an in vitro model a mechanism by which SFRP-4 can modulate a differentiation response to Wnt-3a. © 2008 Constantinou et al; licensee BioMed Central Ltd.